Pengembangan Media Pembelajaran Timecomm Augmented Reality Pada Kelas X DKV Di SMK Negeri 1 Gorontalo - Haikal Z.W Isa; Dian Novian; Arif Dwinanto; Mukhlisulfatih Latief; Eka V. Dangkua (Transbahasa, 2026)
The use of learning media in the Basic Competencies of Visual Communication Design (DKV) subject at SMK Negeri 1 Gorontalo remains limited. The learning process is still dominated by conventional teaching methods and media that are unable to effectively visualize the development of visual communication design industry technology in a concrete and interactive manner. As a result, students tend to be passive, show low engagement, and experience difficulties in understanding historical and abstract learning materials. This study aimed to develop an Augmented Reality (AR)-based learning media for the topic of the Development of Visual Communication Design Industry Technology and to evaluate its feasibility and practicality for Grade 10 DKV students at SMK Negeri 1 Gorontalo. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. Data were collected through validation by media experts and subject-matter experts, as well as a practicality test involving 26 Grade 10 DKV students. The results showed that the developed learning media achieved a feasibility score of 93.22% from subject-matter experts and 90.40% from media experts, both categorized as Very Feasible. Furthermore, the practicality test yielded a score of 89.22%, which was also categorized as Very Feasible. These findings indicate that the developed Augmented Reality-based learning media is feasible and practical for classroom implementation. The media provides interactive three-dimensional visualization of learning objects and has the potential to enhance students' engagement, participation, and understanding of the learning materials.